The association of surgical approach and bearing size and type with dislocation in total hip arthroplasty for acute hip fracture. (1st July 2022) - Rogmark, Cecilia; Nåtman, Jonatan; Jobory, Ammar; Hailer, Nils P.; Cnudde, Peter
Abstract : Aims: Patients with femoral neck fractures (FNFs) treated with total hip arthroplasty (THA) have an almost ten-fold increased risk of dislocation compared to patients undergoing elective THA. The surgical approach influences the risk of dislocation. To date, the influence of differing head sizes and dual-mobility components (DMCs) on the risk of dislocation has not been well studied. Methods: In an observational cohort study on 8, 031 FNF patients with THA between January 2005 and December 2014, Swedish Arthroplasty Register data were linked with the National Patient Register, recording the total dislocation rates at one year and revision rates at three years after surgery. The cumulative incidence of events was estimated using the Kaplan-Meier method. Cox multivariable regression models were fitted to calculate adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) for the risk of dislocation, revision, or mortality, stratified by surgical approach. Results: The cumulative dislocation rate at one year was 8.3% (95% CI 7.3 to 9.3) for patients operated on using the posterior approach and 2.7% (95% CI 2.2 to 3.2) when using the direct lateral approach. In the posterior approach group, use of DMC was associated with reduced adjusted risk of dislocation compared to 32 mm heads (HR 0.21 (95% CI 0.07 to 0.68); p = 0.009). This risk was increased with head sizes < 32 mm (HR 1.47 (95% CI 1.10 to 1.98); p = 0.010). Neither DMC nor different head sizes influenced the risk of revision following the posterior approach. Neither articulation was associated with a statistically significantly reduced adjusted risk of dislocation in patients where the direct lateral approach was performed, although this risk was estimated to be HR 0.14 (95% CI 0.02 to 1.02; p = 0.053) after the use of DMC. DMC inserted through a direct lateral approach was associated with a reduced risk of revision for any reason versus THA with 32 mm heads (HR 0.36 (95% CI 0.13 to 0.99); p = 0.047). Conclusion: When using a posterior approach for THA in FNF patients, DMC reduces the risk of dislocation, while a non-significant risk reduction is seen for DMC after use of the direct lateral approach. The direct lateral approach is protective against dislocation and is also associated with a lower rate of revision at three years, compared to the posterior approach. Cite this article: Bone Joint J  2022;104-B(7):844–851.